TRAP CROPS FOR THE CONTROL OF THE TOBACCO STEM BORER Faustinus apicalis (Faust) (Coleoptera: Curculionidae) - SOTO-GIRALDO, ALBERTO (Revista Colombiana de Entomología, 1993)
The tobacco stem borer is the insect pest that causes the, lightest economic losses to tobacco growers in the Colombian Caribbean Coast. The present work aimed at controlling this stem borer through the use of trap crops. Thus, the following materials were used: the tomato Roma VF, the eggplant Black Beauty, a sunflower cultivar, and a tobacco cultivar. Around the tobacco plots, 3 rows of the trap crop used were sown 30 days before the tobacco planting. It was observed that the adults of the stem borer have a strong preference for the eggplant. When this plant species protected the tobacco plots, this crop suffered a very mild attack of the insect pest and gave superior yields (42,6% higher than the check). The quality of the harvest classes was also better compared with that of the other treatments.